2020
DOI: 10.1159/000510813
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Lambs with Myelomeningocele Repaired in utero with Placental Mesenchymal Stromal Cells for 6 Months: A Pilot Study

Abstract: <b><i>Background:</i></b> Fetal repair of myelomeningocele (MMC) with placental mesenchymal stromal cells (PMSCs) rescues ambulation in the ovine model up to 48 h postnatally. Outcomes past 48 h are unknown as MMC lambs have not been survived past this timepoint. <b><i>Objective:</i></b> We aimed to survive lambs for 6 months following the fetal repair of MMC with PMSCs. <b><i>Methods:</i></b> Fetal MMC lambs were repaired with PMSCs. Lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, long-term outcomes would be informative regarding the durability of our findings. We have previously shown that the improvements in distal motor function afforded by in utero application of the PMSC-ECM to the spinal cord are durable to 6 months of age [ 43 ] and we hypothesize that the bowel and bladder functionality observed in this study may be similarly durable.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, long-term outcomes would be informative regarding the durability of our findings. We have previously shown that the improvements in distal motor function afforded by in utero application of the PMSC-ECM to the spinal cord are durable to 6 months of age [ 43 ] and we hypothesize that the bowel and bladder functionality observed in this study may be similarly durable.…”
Section: Discussionmentioning
confidence: 59%
“…In particular, to prevent the natural healing of the MMC defect that is seen in the fetus [ 41 ], surgical MMC defect creation involves removal of the paraspinal muscles in addition to the lamina and dura, resulting in increasing spinal column angulation and instability with growth of the animal [ 42 ]. This limits the ability to study long-term outcomes due to the intense rehabilitation and veterinary care required to sustain these animals long-term [ 43 ]. However, long-term outcomes would be informative regarding the durability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the application of placental mesenchymal stromal cells seeded on to extracellular matrix improved the motor function in these animals, as we have demonstrated in other models [22-24]. However, even with the incorporation of placental mesenchymal stromal cells we have previously been able to survive only 1 lamb for a long term with our prior fetal surgical model [27].…”
Section: Discussionmentioning
confidence: 76%
“…Occasionally, studies followed lambs up to 1 week of age [20]. In our prior attempts at long-term survival, 5 out of 6 lambs began developing worsening motor function within 1 week [27]. We have previously demonstrated the long-term survival to 6 months of 1 lamb that underwent in utero MMC defect creation and repair, which was possible with the addition of physical therapy and bracing orthotic devices [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation